Analysis the effect of globalization and uncertainty on trade openness in ASEAN: A panel quantile regression approach - Khalil, Amber; Abadi, Rifky Prasetya; Nasir, Muhammad Safar (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Trade openness is defined as a country's involvement in the global economy through international trade, foreign investment, and capital flows. High levels of trade openness enable countries to capitalize on the vast global market, access foreign technology and capital, and increase economic efficiency and competitiveness. This study focuses on the determinants of trade openness and the institutional environment. This is inseparable from the fact that ASEAN countries have more developing countries than developed countries, so that global shocks have an impact on the domestic economy. This study used a panel quantile regression The findings show globalization has an effect at the quantile levels of 0.25, 0.50, and 0.75 and indicates that increasing globalization also increases trade openness. As globalization increases, socio-economic relations between countries also improve, such as expanding relations between countries for international cooperation and at the 0.90 quantile level, globalization has no effect on trade openness. This means that high levels of globalization do not affect trade openness. The panel quantile ​​of 0.10, 0.25, 0.50, 0.75, and 0.90 indicates that economic uncertainty has no effect on trade openness means countries on economic recovery, the government still applies international trade restrictions to protect domestic entrepreneurs. The implication of the study for the policymakers that need to increase the globalization index to not only foreign trade occurs, but also technology transfer that can encourage high-quality and globally competitive domestic production, thereby supporting the trade-led growth hypothesis.